Risk factors associated to main forms of early neonatal sepsis. Cartagena. Colombia. 2013 - Jaime Lorduy Gómez; Stephanye Carrillo González; Shirley Fernández Aragón; Álvaro Quintana Salcedo (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: Despite of advances in antibiotic therapy, of supporting measures and knowledge of the factors of infectious risk, early neonatal sepsis remains an important and absurd cause high mortality and morbility in the neonatal intensive care units. Every year in the world more than 4 million children died during the neonatal period, which is the highest probability period of death. Objective: To determine the main risk factors associated with the main forms of early neonatal sepsis in Cartagena, Colombia. Materials and Methods: Was performed a retrospective, cross-sectional and descriptive study. The information's sources are secondary. 130 records of newborns with early diagnosis of sepsis were taken. Was also performed an univariate and bivariate analysis to establish the relationship tendency between obstetric and neonatal variables with forms of early neonatal sepsis by means of Chi square and p value <0.05. They also calculated the Odds Ratio (OR) as a measure of risk and their respective confidence intervals. Results: In the 39.2% of cases the main cause of early sepsis corresponds to pneumonia, 22.3% bacteremia and 0.8% represents meningitis' cases. Were few obstetric variables associated with early neonatal sepsis, only chorioamnionitis was recognized as the leading cause of pneumonia. Conclusions: The socio-demographic and obstetric factors were found not very associated with cases of early sepsis. The main neonatal factors are those that best explain the cases of early neonatal sepsis. Keywords: Newborn, risk factors, sepsis, vertical transmission of infectious disease.